Short review on the atmospheric bioaerosols. Issue 1 (March 2021) - Emetere, M.E.; Oloke, O.C.; Afolalu, S.A.; Joshua, O.
Abstract: The variability of bioaerosols cut across seasonal changes, indoor encasements, outdoor sources, and atmospheric conditions. Hence, the easiest way to curb disease-carrying bioaerosols requires an in-depth understanding of the factors mentioned above. In this short review, the physical and biological properties of bioaerosols were discussed. It was discovered that its biological and physical properties are salient to determine its diffusion, deposition, control, and measurement.